Drosophila DJ-1 Mutants Are Selectively Sensitive to Environmental Toxins Associated with Parkinson's Disease. - Meulener, M.; Whitworth, A.J.; Armstrong-Gold, C.E.; Rizzu, P.; Heutink, P.; Wes, P.D.; Pallanck, L.J.; Bonini, N.M. (Current Biology, 2005)
Parkinson's disease (PD) is a common neurodegenerative disorder that displays both sporadic and inherited forms. Exposure to several common environmental toxins acting through oxidative stress has been shown to be associated with PD. One recently identified inherited PD gene, DJ-1, may have a role in protection from oxidative stress, thus potentially linking a genetic cause with critical environmental risk factors. To develop an animal model that would allow integrative study of genetic and environmental influences, we have generated Drosophila lacking DJ-1 function. Fly DJ-1 homologs exhibit differential expression: DJ-1beta is ubiquitous, while DJ-1alpha is predominantly expressed in the male germline. DJ-1alpha and DJ-1beta double knockout flies are viable, fertile, and have a normal lifespan; however, they display a striking selective sensitivity to those environmental agents, including paraquat and rotenone, linked to PD in humans. This sensitivity results primarily from loss of DJ-1beta protein, which also becomes modified upon oxidative stress. These studies demonstrate that fly DJ-1 activity is selectively involved in protection from environmental oxidative insult in vivo and that the DJ-1beta protein is biochemically responsive to oxidative stress. Study of these flies will provide insight into the critical interplay of genetics and environment in PD.